Retears of the Rotator Cuff: An Ultrasonographic Assessment During the First Postoperative Year. Issue 12 (19th December 2019) - Aguado, Giussepe; Obando, Daniel Vernaza; Herrera, Gilberto A.; Ramirez, Alejandro; Llinás, Paulo J.
Background: Surgical repair of rotator cuff (RC) tears is an effective treatment option. However, the prevalence of recurrent ruptures is high. Hypothesis: Recurrent tears are a frequent complication of surgical repair of RC tears. Their incidence might be influenced by factors such as the patient's age and size of the initial tear. Study Design: Case series; Level of evidence, 4. Methods: Data from 90 adult patients who underwent arthroscopic RC repair between 2014 and 2017 and underwent an ultrasound examination 6 to 12 months after surgery were analyzed retrospectively. Massive tears were repaired using a double-row technique, and nonmassive tears were repaired with a single-row technique. Clinical records were reviewed for demographic information. Results: All patients (57.8% women; 42.2% men) were older than 18 years (mean, 58.9 years). Of these patients, 30.0% (27/90) had massive tears, which were primarily found in patients ≥60 years (74.1%; 20/27). Complete healing was seen in 74.5% of all repairs during follow-up. A total of 23 patients (25.5%) had retears (13 complete; 10 partial), which were diagnosed by ultrasound imaging 6 to 12 months after the initial surgery. The occurrence of retears was more prevalent in patients with massive tears than in patients with nonmassive tears (40.7% vs 19.0%, respectively); the difference was statistically significant ( P = .03). Reruptures occurred in 50.0% of patients older than 60 years with massive tears. Although patients older than 60 years had more recurrent tears (32.6%) compared with younger patients (18.2%), the difference was not statistically significant ( P = .12). Conclusion: One-quarter of the patients who had undergone surgical repair of an RC tear had recurrent ruptures. There was a statistically significant association between the initial massive tear and a retear. Patients older than 60 years showed a higher recurrence rate, but this difference lacked statistical significance. Reruptures occurred in 50.0% of patients older than 60 years with massive tears.